The exceptional child : inclusion in early childhood education - Allen, K. Eileen, 1918-2015; Cowdery, Glynnis Edwards (Wadsworth Cengage Learning, 2012)
"The exceptional child: inclusion in early childhood education, is the most comprehensive and applied text available on early childhood special education. The text covers foundational issues facing teachers, parents, and paraprofessionals working in inclusive early childhood settings. It begins with definitions and explanations of key topics such as inclusion, federal legislation related to young children with disabilities, and different kinds of disabilities that early childhood educators may encounter in their programs. Then, it covers various applied issues and strategies related to early childhood inclusion--such as how to teach effectively and how to manage problematic behaviors. The Developmental Behavioral approach and the importance of classroom arrangement are stressed throughout. Current research related to early childhood education and inclusion is also cited. The authors explain how to effectively work with a diverse group of children that may contain more than one child with significant challenges, and how to design optimal learning at the individual and group levels. In addition, the authors address how to give parents and caregivers a role in the special education process while encouraging children to gain independence and facilitating their self-care."
"International edition"--Z obálky
Terminologický slovník
Keywords: speciální pedagogika; děti se zdravotním postižením; děti s mentálním postižením; integrovaná výchova a vzdělávání; speciální vzdělávací potřeby; special education; children with disabilities; children with mental disabilities; integrated education; special educational needs; učebnice; textbooks